The Association of Allergy and Systemic Lupus Erythematosus as a Single Disease and an Overlapping Syndrome compared to Control Group (Bangladesh Journal of Medical Science, 2024)
Allergic diseases and systemic lupus erythematosus (SLE) sometimes are being connected since both of these diseases are affected by gene-environment processes. SLE can appear coexisting with other autoimmune diseases as an overlapping syndrome. This research was done to investigate the relation of allergic diseases and SLE as a single SLE or overlapping syndrome compared to control. We collected datas from 39 SLE only, 22 overlapping syndrome SLE, and 39 non SLE subjects who had filled an online Score for Allergic Rhinitis (SFAR) questionnaire. There are significant outcomes of the existance of allergic disease (p=.007), atopic dermatitis (p=.000) and total number of allergies (p=.016) in SLE patients. There is a correlation of the appearance of allergy in SLE as a single or coexisting with other autoimmune disease compared to control group. Atopic dermatitis and the more number of allergic diseases that the one have, play role in appearing SLE.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 551-554